Gene of the month: ERG. Issue 9 (23rd June 2022) - Mullen, Dorinda; Nowak, Klaudia; Chetty, Runjan
Abstract : The ERG gene belongs to the erythroblastosis transformation specific family of transcription factors and encodes for the transcription regulator protein ERG. It is located on chromosome 22q22 and is a nuclear transcription factor. In normal physiology, ERG protein is expressed in endothelial cells and is involved in processes including, but not limited to, angiogenesis and haematopoiesis. Of diagnostic value in clinical practice, ERG immunohistochemistry is a useful marker of endothelial differentiation for both benign and malignant vascular lesions. It is also reliable for identifying ERG gene translocated malignancies such as EWS/FUS::ERG Ewing's sarcoma and TMPSSR2::ERG prostatic carcinoma.